Translanguaging Ruang Digital Urban dalam Video Youtube Shorts tentang Industri Otomotif Cina - Pratista Shafa Brillian; Byvan Quai Alkana; Bagaskara Wijayakusuma (Lingua Franca, 2025)
The rapid development of digital media has significantly transformed language practices in urban societies, particularly through short video platforms such as YouTube Shorts, where communication is fast and dynamic. One phenomenon that emerging in this context is translanguaging, understood as the flexible use of multiple linguistic repertoires to construct meaning, negotiate identity, and manage social interaction. This study investigates translanguaging practices in a YouTube Shorts video featuring a senior automotive journalist discussing the Chinese automotive industry. Employing a qualitative approach with digital discourse and multimodal analysis, this research explores how translanguaging functions within short-form digital content and how it contributes to identity construction in an urban digital context. The findings indicate that translanguaging is not merely a linguistic strategy, but also a social and performative practice shaped by the affordances of short video platforms. It enables speakers to position themselves professionally, engage audiences effectively, and align with specific digital and interest-based communities. By situating the analysis within contemporary theories of translanguaging and sociolinguistic identity, this study demonstrates how language use in YouTube Shorts reflects broader dynamics of digital communication and globalization. The study contributes to digital sociolinguistics by highlighting the role of translanguaging in short video discourse and offers insights into how multilingual practices operate in emerging media environments.